If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1.5m + 3) = 3.5m + -1 Reorder the terms: 2(3 + 1.5m) = 3.5m + -1 (3 * 2 + 1.5m * 2) = 3.5m + -1 (6 + 3m) = 3.5m + -1 Reorder the terms: 6 + 3m = -1 + 3.5m Solving 6 + 3m = -1 + 3.5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3.5m' to each side of the equation. 6 + 3m + -3.5m = -1 + 3.5m + -3.5m Combine like terms: 3m + -3.5m = -0.5m 6 + -0.5m = -1 + 3.5m + -3.5m Combine like terms: 3.5m + -3.5m = 0.0 6 + -0.5m = -1 + 0.0 6 + -0.5m = -1 Add '-6' to each side of the equation. 6 + -6 + -0.5m = -1 + -6 Combine like terms: 6 + -6 = 0 0 + -0.5m = -1 + -6 -0.5m = -1 + -6 Combine like terms: -1 + -6 = -7 -0.5m = -7 Divide each side by '-0.5'. m = 14 Simplifying m = 14
| -12+3n=4n+7(n+4) | | 2(x+-4)+2x=4x+-1 | | 8+6n=8(1+6n)+3n | | 4(a+5)=28+4a | | 5p+6=-4-8 | | 6(x+6)=29+7x | | 3(x-3)=5(1.5+x) | | 2c+9=4c-9 | | 2x+10+3x=0 | | -3x-2+5x=12 | | 2a-2=3a+3 | | 14=-8x+-10 | | 3+6z=13+6z | | 1.5x-1.5=0 | | 4x+3x-9=5 | | 3(4x-9)=5(2x-5) | | 5n-6=24 | | 7x-10=6(11-2x) | | 8c+10=2(4c+5) | | 2(h-8)-h=h-16 | | 1.6(3y-1)+2=5y | | 12c+15=24 | | 5(2-x)=7x-26 | | 37+8x=4(7-x) | | 8n+6=46 | | -6+7=3(2p-3)-4(-10+4p) | | 5y=2y-42-3y | | -3x=45 | | 4x=-60 | | 6x+3=-5x+14 | | 90-(12-8y)=150 | | 5x+8-3x+2=20 |